Influence of metal powder characteristics on product quality with directed energy deposition of Inconel 625. Issue 1 (2016) - Kakinuma, Yasuhiro; Mori, Masahiko; Oda, Yohei; Mori, Takanori; Kashihara, Makoto; Hansel, Adam; Fujishima, Makoto
Abstract: Directed energy deposition (DED) for producing a complex shaped metal part has attracted attention in the aerospace industry. However, DED easily causes structural defects such as voids and compositional changes, which results in the deterioration of the mechanical strength of the product. Hence, reducing such defects is essential. In this study, the influence of the powder characteristics of Inconel 625 was focused upon, and the void density and compositional change inside the deposited part were analyzed. The results indicated that a slight amount of carbon in the particle caused void generation and a carbon layer was formed at the surface.